Bacterial Contamination of Computer and Hand Hygiene Compliance in the Emergency Department. Issue 6 (November 2013) - Hong, DY; Park, SO; Lee, KR; Baek, KJ; Moon, HW; Han, SB; Shin, DH
Introduction: The aim of this study was to determine the degree and nature of bacterial contamination of computer equipment in three Korean emergency departments (ED). Methods: Hand hygiene practices of ED doctors and nurses were observed before contact with computer equipment. Microbiological swab samples were obtained from 112 multiple-user computer keyboards and electronic mice in the ED of three teaching hospitals. Isolated organisms were identified by a clinical microbiologist using Gram stain, colony morphology, and susceptibility test. Results: Of the 112 samples, 103 (92.0%) showed growth of organisms on culture. Thirty-eight (33.9%) pieces of computer equipment yielded multiple bacterial species. Coagulase-negative Staphylococcus was the most common microorganism isolated (85.7%). Methicillin-resistant Staphylococcus aureus was obtained from two keyboards in two hospitals (1.8%). Hand hygiene compliance was observed on 29.9% occasions. Hand hygiene compliance after patient contact (38.0%) was higher than after other environmental contact (20.7%). Conclusions: Multiple user computer equipment in the ED may serve as reservoirs for nosocomial infection. Hand hygiene should be performed before and after using all ED equipment, including computer equipment. (Hong Kong j.emerg.med. 2012;19:387-393)